A cross layer approach for packet scheduling at downlink of WiMAX IEEE802.16e - Shu'aibu, Dahiru Sani (EuroJournals, Inc., 2010)
WiMAX is one of the broadband wireless access networks with promising technology for providing better coverage and quality of service (QoS) to subscribers in the network. It supports different scheduling services with different QoS requirements the challenge here is how to efficiently scheduling the packets of subscribers having different QoS queuing in different buffers? We proposed a new algorithm capable of scheduling of all service flows type considering the nature of the wireless link, delay and buffer size. Performance of the proposed algorithm is evaluated by computer simulations it showed that the algorithm developed has achieved high throughput and good frame utilization.